2016
DOI: 10.1016/j.celrep.2016.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 21 Mediates Glycemic Regulation by Hepatic JNK

Abstract: The cJun NH2-terminal kinase (JNK) signaling pathway is implicated in metabolic syndrome, including dysregulated blood glucose concentration and insulin resistance. Fibroblast growth factor 21 (FGF21) is a target of the hepatic JNK signaling pathway and may contribute to the regulation of glycemia. To test the role of FGF21, we established mice with selective ablation of the Fgf21 gene in hepatocytes. FGF21-deficiency in the liver caused marked loss of FGF21 protein circulating in the blood. Moreover, the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 35 publications
0
42
0
Order By: Relevance
“…Tyrosine phosphorylation and associated signaling cascades are an important layer of regulation of cell behavior and phenotypic changes. With the exception of two recent global phosphorylation studies (Krahmer et al , ; Li et al , ), signaling modifications associated with excess lipid accumulation (e.g., triglycerides, FFAs, ceramides) have so far been focused on individual signal transduction nodes that have been found to play important roles in insulin resistance‐associated inflammation, lipotoxicity, and metabolic reprogramming (Aguirre et al , ; Özcan et al , ; Fediuc et al , ; Han et al , ; Vernia et al , , ). However, a systems‐wide view of the impact of calorie overload on tyrosine signaling networks in insulin‐response tissues has been missing.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine phosphorylation and associated signaling cascades are an important layer of regulation of cell behavior and phenotypic changes. With the exception of two recent global phosphorylation studies (Krahmer et al , ; Li et al , ), signaling modifications associated with excess lipid accumulation (e.g., triglycerides, FFAs, ceramides) have so far been focused on individual signal transduction nodes that have been found to play important roles in insulin resistance‐associated inflammation, lipotoxicity, and metabolic reprogramming (Aguirre et al , ; Özcan et al , ; Fediuc et al , ; Han et al , ; Vernia et al , , ). However, a systems‐wide view of the impact of calorie overload on tyrosine signaling networks in insulin‐response tissues has been missing.…”
Section: Discussionmentioning
confidence: 99%
“…Postprandial increases in insulin levels which, serves to shut down the synthesis and storage of lipids, has been reported to be accompanied by a decrease in JNK activation [22]. In mice lacking the expression of hepatic JNK1 and JNK2 the expression of the peroxisome proliferator-activated receptor-alpha (PPARα) and its target genes involved in oxidative metabolism that enhances hepatic β-oxidation are activated [23] thereby, increasing lipid breakdown under conditions of reduced nutritional load.…”
Section: Jnk In Hepatic Metabolism and Pathophysiologymentioning
confidence: 99%
“…Hence, it is proposed that hepatic JNK mediates the fasting and feeding cues of circulating FGF21 expression [23]. In contrast to the studies by Vernia et al [22, 23], it has also been reported that p38α/β MAPK, rather than JNK, is involved in the regulation of FGF21 [25]. Mice lacking the expression of MKP-1 in the liver exhibit decreased levels of circulating FGF21 under conditions in which both hepatic p38α/β MAPK and JNK are elevated [25].…”
Section: Jnk In Hepatic Metabolism and Pathophysiologymentioning
confidence: 99%
“…Part of this protection may be mediated by increased FGF21 secretion, as double JNK1 and JNK2 KO upregulated the mRNA expression of FGF21. FGF21 can enhance whole body insulin sensitivity by increasing adiponectin and energy expenditure [101,102]. With regard to the role of JNK in hepatic steatosis, hepatocyte-specific JNK1-null mice developed hepatic steatosis and had significantly higher Srebp-1 expression compared to wild-type mice [98].…”
Section: Livermentioning
confidence: 99%